Análisis de artículos tecnológicos para fomentar la lectura en los estudiantes del décimo grado del colegio de bachillerato internacional “Adolfo Valarezo” de la ciudad de Loja en la asignatura de matemática durante el año lectivo 2014 – 2015. Propuesta alternativa - Imaicela Rosillo, Juan Luis (2015)
This thesis refers to "ANALYSIS OF TECHNOLOGICAL ITEMS TO PROMOTE READING AT THE TENTH GRADE STUDENTS SCHOOL OF INTERNATIONAL BACHELOR" ADOLFO VALAREZO "of the city of Loja in math classes during the school year 2014 - 2015. ALTERNATIVE PROPOSAL ". To which we must ask how to encourage reading among tenth graders based on technological items? How to apply ICT-based strategies to improve reading comprehension among students in tenth grade? The general objective was: Analyze technological items to encourage reading in the tenth grade students of the College of International Baccalaureate "Adolfo Valarezo" The methods that have been used in the development of this research were: inductive, analytical. Study types: exploratory, descriptive and explanatory. Statistical model used survey techniques aimed at students and two teachers interviews applied math tenth year and the authorities of the institution in order to investigate the reading process currently gives. After the implementation of the survey to students concludes that most students have a preference for literary, scientific and technological items, which should be included in the form of design results, as well as great preference silent reading, which students can provide their own knowledge, but also because it is considered harmful omitting share with others also used the hours students to read is not considered the most adequate because people do not have a regular schedule for reading, which should be considered is to pace yourself weekly reading devoted entirely to read, you can achieve by reducing the amount of hours that television is observed. Moreover, the use of ICT tools for the design of educational activities that enhance the teaching-learning process of students is recommended, as well as restricting the use of social networks and internet devices for gaming purposes or related aspects. Finally an alternative proposal that is being considered by the authorities, teachers of the institution, in order to implement to improve the habits of students in technological items and therefore a better performance in the subject of mathematics arises.